The impact of a low-calorie, low-glycemic diet on systemic lupus erythematosus: a systematic review - Aline Mizusaki Imoto (BMC, 2021)
Abstract Background Diet plays a critical role in Systemic Lupus Erythematosus (SLE) patients, impacting on the microbiota composition and, consequently, on the immune response. The objective was to analyze and verify the diet effect on SLE patients. Methods This is a systematic review performed at the Evidences-based Health Lab, Escola Superior em Ciências da Saúde, Brasília (DF), Brazil. In March, 2021, five databases, and grey literature, through JSTOR, Open Grey, and Google Scholar were searched. Randomized Clinical Trials in which SLE patients with calorie restricted, low glycemic index or other diet involving the joint adequacy of these aspects, compared with placebo or different types of diet, were included. Results It was identified in the databases 758 articles; 132 were duplicated; 616 references were screened, and 604 were excluded. After reading the title and abstract, 12 articles were included for full-text reading. After the full-text reading, three studies were included for quantitative analysis. The diet improved the quality of life at 6 (MD 16.30; 5.91;26.69) and 12 weeks (MD 14.60; 0.88;28.32). The GRADE was used to evaluate the quality of evidence. Conclusion There is low evidence that the diet has a positive impact on the quality of life of SLE patients. Trial registration PROSPERO—CRD4202012208.